Anisotropy of the interface tension of the three-dimensional Ising model - Bittner, Elmar; Nuβbaumer, Andreas; Janke, Wolfhard (Nuclear physics. B, Particle physics, 2009)
We determine the interface tension for the 100, 110 and 111 interface of the simple cubic Ising model with nearest-neighbour interaction using novel simulation methods. To overcome the droplet/strip transition and the droplet nucleation barrier we use a newly developed combination of the multimagnetic algorithm with the parallel tempering method. We investigate a large range of inverse temperatures to study the anisotropy of the interface tension in detail.
Gesehen am 11.10.2022